Posterior Malleolar Fractures: A Critical Analysis Review - Rammelt, Stefan; Bartoníček, Jan (JBJS reviews, 2020)
In patients with ankle fractures, the presence of a posterior malleolar fracture has a negative impact on the prognosis. Computed tomography (CT) scanning is essential for fracture classification and treatment planning, as the indication for surgery depends on the 3-dimensional fragment outline and displacement, incisura involvement, and the presence of joint impaction. Anatomic reduction of a posterior malleolar fragment restores the incisura, facilitating reduction of the distal part of the fibula, and it also restores the integrity of the posterior portion of the syndesmosis, reducing the need for additional syndesmotic stabilization. Direct open reduction and fixation of posterior malleolar fragments from a posterior orientation is biomechanically more stable and provides a more accurate reduction than does indirect reduction and anterior-to-posterior screw fixation. Intra-articular step-off of >=2 mm is an independent risk factor for an inferior outcome and the development of posttraumatic arthritis, irrespective of the fragment size.
Keywords: Fracture Fixation, Internal; vnitřní fixace fraktury; poranění kotníku; Humans; fraktury tibie; lidé; Tibial Fractures; Ankle Injuries; Prognosis; prognóza